In silico characterization of the interaction between LSKL peptide, a LAP-TGF-beta derived peptide, and ADAMTS1. (April 2016) - Laurent, Marie-Amandine; Bonnier, Dominique; Théret, Nathalie; Tufféry, Pierre; Moroy, Gautier
Graphical abstract: Binding mode of LSKL peptide, in cyan, with ADAMTS1, in wheat color. The nonbonded interactions are represented in yellow dashed lines. The binding sequence of ADAMTS1 is colored in red. Highlights: We have experimentally shown that TSP-1 domain of ADAMTS1 is able to bind TGF-β. Docking experiments confirm that KTFR sequence interacts with LSKL peptide. MD simulations reach a stable binding mode between TSP-1 domain and LSKL peptide. Abstract: Metalloproteases involved in extracellular matrix remodeling play a pivotal role in cell response by regulating the bioavailability of cytokines and growth factors. Recently, the disintegrin and metalloprotease, ADAMTS1 has been demonstrated to be able to activate the transforming growth factor TGF-β, a major factor in fibrosis and cancer. The KTFR sequence from ADAMTS1 is responsible for the interaction with the LSKL peptide from the latent form of TGF-β, leading to its activation. While the atomic details of the interaction site can be the basis of the rational design of efficient inhibitory molecules, the binding mode of interaction is totally unknown. In this study, we show that recombinant fragments of human ADAMTS1 containing KTFR sequence keep the ability to bind the latent form of TGF-β. The recombinant fragment with the best affinity is modeled to investigate the binding mode of LSKL peptide with ADAMTS1 at the atomic level. Using a combined approach with molecular docking and multiple independent molecular dynamics (MD) simulations, we provide the binding mode of LSKL peptide with ADAMTS1. The MD simulations starting with the two lowest energy model predicted by molecular docking shows stable interactions characterized by 3 salt bridges (K3 –NH3 + with E626 –COO − ; L4 –COO − with K619 –NH3 + ; L1 –NH3 + with E624 –COO − ) and 2 hydrogen bonds (S2 –OH with E623 –COO − ; L4 –NH with E623 –COO − ). The knowledge of this interaction mechanism paves the way to the design of more potent and more specific inhibitors against the inappropriate activation of TGF-β by ADAMTS1 in liver diseases.